Individualization of levodopa treatment using a microtablet dispenser and ambulatory accelerometry. (25th January 2018) - Johansson, Dongni; Ericsson, Anders; Johansson, Anders; Medvedev, Alexander; Nyholm, Dag; Ohlsson, Fredrik; Senek, Marina; Spira, Jack; Thomas, Ilias; Westin, Jerker; Bergquist, Filip
Summary: Aim: This 4‐week open‐label observational study describes the effect of introducing a microtablet dose dispenser and adjusting doses based on objective free‐living motor symptom monitoring in individuals with Parkinson's disease (PD). Methods: Twenty‐eight outpatients with PD on stable levodopa treatment with dose intervals of ≤4 hour had their daytime doses of levodopa replaced with levodopa/carbidopa microtablets, 5/1.25 mg (LC‐5) delivered from a dose dispenser device with programmable reminders. After 2 weeks, doses were adjusted based on ambulatory accelerometry and clinical monitoring. Results: Twenty‐four participants completed the study per protocol. The daily levodopa dose was increased by 15% (112 mg, P  < 0.001) from period 1 to 2, and the dose interval was reduced by 12% (22 minutes, P  = 0.003). The treatment adherence to LC‐5 was high in both periods. The MDS‐UPDRS parts II and III, disease‐specific quality of life (PDQ‐8), wearing‐off symptoms (WOQ‐19), and nonmotor symptoms (NMS Quest) improved after dose titration, but the generic quality‐of‐life measure EQ‐5D‐5L did not. Blinded expert evaluation of accelerometry results demonstrated improvement in 60% of subjects and worsening in 25%. Conclusions: The introduction of a levodopa microtablet dispenser and accelerometry aided dose adjustments improve PD symptoms and quality of life in the short term.